Osteosynthesis in Osteogenesis Imperfecta, telescopic versus non-telescopic nailing - Sterian, A (J Med Life, 2015)
The paper refers to a pediatric patient suffering from Osteogenesis Imperfecta that was diagnosed soon after birth, after suffering from an intrauterine fracture of the femur in the 7th month of pregnancy. The beginning of the presentation contains some general considerations regarding the illness and the treatment done up to the point when the first telescopic rod was used. Following the evolution of the child from birth to the age of 7 years, we could trace a line of evolution under several methods of treatment, surgical or conservative, and also on different surgical treatment variants and their outcome during growth. Together with the X-rays that documented each step of the treatment, we could affirm for sure that both clinically and radiologically, the best results were obtained after the last 4 interventions, when all 4 major bones of the lower limbs were operated on. Until the moment Fassier–Duval nails were used, the evolution of the illness and the complications that appeared after certain surgery procedures were not so good. Several procedures had to be revised because of nail or pin displacement and eventually the patient lost the walking capability. The main problem with non telescopic treatment was the lack of stability that the bone needed to have after an open surgery for deformity correction, and up to that moment, the methods used were not designed to work on the long term; even in the best circumstances, the patient had to go to the OR for nail replacement after the bone outgrew it.